Balanced Scorecard : A Strategy Business Solutions - Susiani, Dena Evi (PRESTASI, 2012)
Many employers are experiencing difficulty in defining business strategy and take measurements on the performance of existing teams and employees in business organizations. so that decisions taken are not appropriate and likely wrong direction, and can be more detrimental in various aspects of the business.The balanced scorecard has evolved from its early use as a simple performance measurement framework to a full strategic planning and management system. therefore the above condition is so balanced scorecard be one solution for businesses that need a decision right in the face of global competition